Analysis of antiasthmatic drugs for inhalation in the pharmaceutical market of Ukraine and dynamics of their consumption - O. V. Tkachova; Ya. O. Butko (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Bronchial asthma (BA) is a common disease, as today the world suffers from about 300 million people. The number of patients with severe and complicated forms of BA is growing every year due to untimely diagnosis of the disease and late appointment of basic therapy. Complications cause disability in patients and increase mortality. The purpose of this work was to study the range and consumption in Ukraine of antiasthmatic drugs for inhalation (ADI), intended for the treatment of BA for the period 2018-2020. The analysis of the range and volumes of consumption of ADI was carried out according to the system of research of the market of medicines «Pharmstandard» of the company «Morion». Consumption estimates were made using the ATC/DDD methodology. DDDs/1 000 inhabitants/day (DID, DDDs per 1 000 inhabitants per day) was used as a unit of measurement. The results showed that in the pharmaceutical market of Ukraine during 2018-2020 used 61-64 trade names (TN) ADI, of which 11-13 TN were domestically produced and 50-51 TN - foreign manufacturers. Retail prices for ADI during 2018-2020 varied widely and increased slightly each year, due to economic instability in the pharmaceutical market of Ukraine. It was found that the consumption of ADI in the period 2018-2019 increased slightly by 1.03 times - from 7.00 DID in 2018 to 7.24 DID in 2019. In 2020, the consumption of this group of drugs decreased 1.1 times - to 6.60 DID. The undisputed leader in consumption in Ukraine was salbutamol (3.53-3.56 DID), which is probably due to the clinical efficacy and sufficient safety of the drug, greater availability of salbutamol for the population due to the wide range of generic drugs in Ukraine. market and the state program «Affordable Medicines». The second place was taken by the combination of fenoterol + ipratropium bromide (0.81-0.85 DID), which is used in adults and children for the immediate treatment of sudden attacks of bronchospasm in BA. The third place in terms of consumption in Ukraine was occupied by the combination of salmeterol + fluticasone (0.52-0.54 DID), which is mainly prescribed to patients with moderate and severe asthma.